Answer:
$225 a week
Step-by-step explanation:
The opposite is a negative so the answer would be -6
Answer:
x=2; y=-1
Step-by-step explanation:
Hello,
(1) 6x+7y=5
(2) 2x-3y=7
We multiply equation (2) by 3, it gives
6x-9y=21 and we subtract from (1)
6x-9y-6x-7y=-16y=21-5=16
So y = -1
we replace in (1) 6x-7=5 <=> 6x=7+5=12 <=> x =12/6=2
thanks
Answer:
A. Infinitely many
Step-by-step explanation:
9x + 27 = 9(x + 2) + 9
Distribute on the right side.
9x + 27 = 9x + 18 + 9
Combine like terms on the right side.
9x + 27 = 9x + 27
Subtract 27 from both sides.
9x = 9x
Divide both sides by 9.
x = x
x = x is a true statement for every value of x. Therefore, any value you substitute in for x will make the original equation true. That means there is a infinite number of solutions.
Answer: A. Infinitely many
The multiplicative inverse of 1 is in fact 1/1 which is equal to 1. So 1 is actually its own multiplicative inverse.